Ontologies and Semantic Technologies for Intelligence - Obrst, Leo (IOS Press, 2013)
Featuring chapters by selected contributors to the second international Ontology for the Intelligence Community (OIC) conference, this book offers a partial technology roadmap for decision makers in the field of information integration, sharing and situational awareness in the use of ontologies and semantic technologies for intelligence. It focuses on intelligence community needs and the application of ontologies and semantic technologies to assist those needs, including: - sharing information within and among communities, across humans and machines - bringing machines up to the human conceptual level - automating some aspects of intelligence analysis - augmenting the capability to semantically integrate data from all intelligence disciplines - providing analytical tools to exploit available semantically integrated information - assisting semantic disambiguation, reference and correlation of entities, relations and events This work will be of interest not only to US and other intelligence communities (IC), but also to law enforcement and homeland security communities, technical and budgetary decision makers and technologists working in intelligence, including ontologists and ontology developers, computer scientists, software engineers and intelligence analysts; indeed anyone with an interest in semantic technologies and their applications.